SOLIDARITY: RIVAL VERSIONS, CONFLICTING INTERPRETATIONS, AND THE SHAPE OF HOPE - Guyette, Fred (Heythrop journal, 2012)
What do we mean when we utter the word ‘solidarity’? How do we apprehend its meaning when we hear it spoken of by others? The ancient Greeks - Homer, Thucydides, and Aristotle - offer a vantage point from which this inquiry may begin. The Book of Genesis sets before us a cycle of stories about brothers, along with questions about the bonds that keep them together. The sagas of Iceland explore the nature of conflicts between one family and another. Thomas Aquinas gives a distinctive account of solidarity between Christians. Emile Durkheim, too, provides an influential analysis of solidarity. Alexis de Tocqueville, Max Scheler, and Richard Rorty make significant contributions to the discussion. John Paul II elaborated an impressive vision of solidarity. This essay undertakes a form of reconnaissance, then, by exploring the border region between these rival versions of solidarity.